THERAPEUTIC EFFICACY OF POLY-HERBAL FORMULATIONS AND HETEROLOGOUS CUD TRANSPLANTATION WITH PROBIOTICS IN AMELIORATING SIMPLE INDIGESTION IN BUFFALOES - G.C.MOHAN,; B.R.NAIK,; A.C. KUMAR, (International Journal of Pharma and Bio Sciences, 2015)
Therapeutic efficacy of certain poly herbal formulations and probiotics along with heterologous cud transplantation was evaluated in simple indigestion in buffaloes. A total of 18 buffaloes suffering from simple indigestion were treated with Suruchi bolus (10 g twice daily) or Gastricare powder (15g twice daily) or Yeasacc bolus with heterologous cud from healthy sheep. Clinical examination and laboratory analysis of rumen fluid and serum was carried out. Rumen fluid was evaluated for pH, protozoal motility, iodophilic activity, protozoal count, sedimentation activity time, methylene blue reduction time, total protozoa, gas production, ammonia, total volatile fatty acids. In serum, calcium, phosphorus, magnesium, glucose, urea, protein was estimated. All the treatment regimens were successful in ameliorating the changes in rumen liquor and serum biochemical profile. However, treatment with YHC treatment with probiotic Yeasacc bolus + heterologous cud transfer performed better than herbal drugs.